Evaluation of the effect of urine dip vs urine drip on multi‐test strip results. (11th June 2019) - Boag, Alisdair M.; Breheny, Craig; Handel, Ian; Gow, Adam G.
Abstract: Standard operating procedures, including World Health Organization guidelines for packed cell volume, are established for in‐clinic laboratory tests. No independent, evidence‐based guidelines exist for dipstick urinalysis; however, manufacturer's instructions state to dip the stick into urine. In veterinary medicine, small volume urine samples could preclude dipping; therefore, a single drip per pad from a pipette or syringe is often performed. This study aimed to examine the differences between these two urine application methods prior to analysis, with the hypothesis that the method type would not effect on test results of dipstick analysis. To standardize the strip analysis method, a Siemens Clinitek Status + analyzer was used with Multistix10SG dipsticks. Three investigators tested urines from 53 dogs with a range of diseases by both methods. Results were assessed for the degree of agreement between the methods and within method variability. Overall, the agreement between methods was high. Within each method, the drip method variability was higher than that of the dip method ( P = 0.012). Disagreements between methods were present, with pH and blood having the lowest agreement levels. Glucose was more likely to be positive on the drip compared with the dip methodology. This study demonstrates potential clinically relevant differences between the two methods and a higher level of variability with the drip methodology. Therefore, while the drip method could be used for practical reasons (eg, low sample volumes), this study supports the manufacturer's recommended method of dipping the dip stick into urine rather than dripping urine onto each pad with a pipette or syringe.